Study About The Establishment Of Immigration Office Unit In Gadjah Mada University Before And After Authorized Decision Letter By The Director General Of Immigration Number: Imi-0003.Pb.02.09 2021 - Olivia Bianca Chintya Bellisima; Maidah Purwanti; M. Alvi Syahrin (Polteknik Imigrasi, 2022)
Immigration Office Unit in Gadjah Mada University is one of the breakthroughs in helping Immigration duties and Immigration functions by Class I Immigration Office Yogyakarta. Immigration services at that Immigration Office Unit has started since November 25th 2020 (soft launching). Nevertheless, from November 25th 2020 until June 3rd 2021 the authorized decision letter by the director general of immigration related to establishment of Immigration Office Unit in Gadjah Mada University based on article 8 section 1 letter h Director General Immigration Regulations Number: IMI-0746.OT.01.01 2017 about Technical Procedure Establishment of Immigration Office Unit has not been released. Hereafter, this research is to find out how is the role of Immigration Office unit in Gadjah Mada University to support immigration services in Class I immigration Office Yogyakarta and how is the legality of the immigration documents which have been released. The research method is using normative-empirical. As the result, the immigration documents which have been released by that Immigration Office Unit at that period didn’t disturb the legality of documents. However, to make sure that conclusion is strong enough, thing that needed to be done is changing the authorized decision letter about Immigration Office Unit in Gadjah Mada.